Hematologic response and serum and peritoneal fluid proteinogram of cattle affected by intestinal diseases and traumatic reticuloperitonitis - dos Santos, Jomel Francisco; do Rego, Rafael Otaviano; Bastos Afonso, José Augusto; Fagliari, José Jurandir [UNESP]; Silva, Paulo Cesar [UNESP]; Soares, Pierre Castro; de Mendonça, Carla Lopes (Universidade Estadual de Londrina, 2021)
This study aimed to evaluate the hematologic response and the serum and peritoneal fluid (PF) proteinogram of cattle affected by digestive diseases. Twenty-seven animals were distributed in two groups: GI (intestinal diseases) and GII (traumatic reticuloperitonitis, TRP). The animals were previously submitted to a physical exam. Subsequently, blood samples were collected to perform the complete blood count, determine the plasma protein and fibrinogen, and obtain the serum for proteinogram in polyacrylamide gel (SDS-PAGE). Simultaneously, PF was collected to perform physical and chemical evaluation and the electrophoretic profile (SDS-PAGE). ANOVA at the 5% probability level was used to compare the groups. The animals showed signs of apathy, dehydration, and gastrointestinal hypomotility in both groups. However, GI animals showed more significant clinical changes. The blood count of both groups (P > 0.05) showed leukocytosis due to neutrophilia and a regenerative left shift with hyperfibrinogenemia. The proteinogram of both body fluids allowed the identification of proteins albumin (ALB), transferrin (TRF), ceruloplasmin, haptoglobin, α1-acid glycoprotein (α1-AGP), MW 23000 Da, α1-antitrypsin, IgA, and IgG. The [PT] PF/[PT] blood serum ratio of each of the identified proteins increased, showing statistical differences between groups (P < 0.05) regarding PT, ALB, TRF, α1-AGP, and IgG values, with GI animals showing the highest ratio. Intestinal diseases and TRP triggered a systemic and local response characterized by clinical, hematological, and serum and PF proteinogram alterations. The proteins α1-GPA, haptoglobin, and TRF measured in PF were good inflammation biomarkers and useful as an auxiliary tool for the diagnosis and prognosis of digestive diseases in cattle.
Resposta hematológica e proteinograma sérico e do líquido peritoneal de bovinos acometidos com enfermidades intestinais e reticuloperitonite traumática
Keywords: Abdominal fluid; Acute-phase proteins; Cows; Digestive diseases; SDS-PAGE